Cx26 deafness: mutation analysis and clinical variability. Issue 11 (1st November 1999) - Murgia, A; Orzan, E; Polli, R; Martella, M; Vinanzi, C; Leonardi, E; Arslan, E; Zacchello, F
Abstract : Mutations in the gap junction protein connexin 26 ( Cx26 ) gene ( GJB2 ) seem to account for many cases of congenital sensorineural hearing impairment, the reported prevalence being 34-50% in autosomal recessive cases and 10-37% in sporadic cases. The hearing impairment in these patients has been described as severe or profound. We have studied 53 unrelated subjects with congenital non-syndromic sensorineural hearing impairment in order to evaluate the prevalence and type of Cx26 mutations and establish better genotype-phenotype correlation. Mutations in the Cx26 gene were found in 53% of the subjects tested, 35.3% of the autosomal recessive and 60% of the sporadic cases in our series. Three new mutations were identified. The hearing deficit varied from mild to profound even in 35delG homozygotes within the same family. No evidence of progression of the impairment was found. Alterations of the Cx26 gene account for a large proportion of cases of congenital non-syndromic sensorineural deafness, so it seems appropriate to extend the molecular analysis even to subjects with mild or moderate prelingual hearing impairment of unknown cause.